Highly photoluminescence and wide band gap insulating metal hybrid nanoparticles array of samarium-doped SrO:CoO: synthesis, characterizations and sensor characteristics - Adimule, Vinayak; Keri, Rangappa; Rajendrachari, Shashanka; Kendrekar, Pravin; Kulkarni, Chandrashekar V. (Springer, 2023)
In the present work, a new series of Sm-x (x = 1, 6 and 12 wt.%) doped SrO:CoO (1:1) nanocrystals (NCs) have been synthesized by microwave-assisted method. The as-synthesized Sm-x:SrO@CoO NCs were characterized by XRD (X-ray diffraction), UV-visible, SEM (scanning electron microscopy), XPS (X-ray photoelectron spectroscopy), BET (Brunauer-Emmett-Teller) and EDX (energy-dispersive X-ray) spectroscopic investigations. Irregular shaped morphology was revealed from SEM micrographs with average size of the agglomerates similar to 70 nm. XRD patterns confirmed the formation of mixed phase of monoclinic and tetragonal crystal structure. Blueshift in optical absorptivity resulted as Sm concentration increases in NCs and direct optical band gap decreases from 3.12 to 2.21 eV. Photoluminescence (PL) studies showed strong near edge ultraviolet green-yellow emissions for Sm-6 wt.% and12 wt.%:SrO@CoO NCs when excited at 220, 250, 280 nm (lambda(excitation)). Sm-12 wt.%:SrO@CoO NCs showed visible range weak band emissions due to crystal defect and formation of oxygen vacancies. Raman studies of Sm-x:SrO@CoO showed longitudinal optical mode which confirmed the formation of oxygen vacancies. Raman spectroscopy also revealed the presence of Sm-O-Sm, Sr-O-Sr and Co-O bonds in the crystal lattice. In addition Sm6 wt.% and12 wt.%:SrO@CoO NCs showed highest sensitivity (0.10, at 94 mu-ohm and 0.082, at 253 mu-ohm), response (88.9 and 82.7), and had extremely low time parameters (response time of 12, 20 s and recovery time of 24, 44 s) towards O-xylene gas when subjected for detection of its sensitivity in presence of other volatile gases. Moreover sensor exhibited excellent repeatability and restoration. The wide band gap Sm-x:SrO@CoO NCs can find applications in the field of high resistive sensors, display technologies, LEDs, etc.
Keywords: Optical-Properties; Magnetic-Properties; Sm3+ Ions; Luminescence Properties; Williamson-Hall; Green Synthesis; Thin-Films; Co; Performance; Strain